Gender Stereotypes As Hidden Curriculum: A Case of Vietnamese English Textbooks - Phan, Anh; Pham, Tho Xuan (International Journal of Education, 2021)
Gender equality and women empowerment have become a buzzword for development during the past decades with numerous national and international policies, including educational policies. However, gender equality is normally conceptualized in quantitative terms of education such as low disparity in access to education between boys and girls while qualitative aspects of gender equality are still left uncontested, among which is gender stereotypes in hidden curriculum. Gender stereotypes as a social construct, once imbedded in education and educational materials, certainly intervene the gender socialization process of students. The paper attempts to investigate this issue by employing a mixed qualitative and quantitative content analysis of the illustrations in English textbooks for Upper-secondary students in Vietnam. The analysis reveales stereotypes reflected in three main areas: occupations, sports and pastimes, and life duties, all of which confirm social and cultural norms of Vietnamese society towards a woman.